APLIKASI T-SHIRT DESIGN BERBASIS ANDROID DALAM MENUNJANG KREATIFITAS DESAINER - Baco, Irwan (Jurnal Sintaks Logika, 2022)
The rapid development of information technology makes us obligated to be more creative in solving problems in every way, with that software has sprung up with the aim of helping us in our work. One of them is in the field of design and design of t-shirt product development, we are still often confused by the many choices of applications. Therefore, the author has created a T-SHIRT design application where this application can assist designers in designing t-shirts according to designer interactions. This research is an Android-Based T-SHIRT Design Application in Supporting Designer Creativity using a qualitative research type, while the data collection method uses observation, interviews, and literature studies and testing this application using the Black Box and White Box methods.